Nitrogen balance on Costa Rican dairy farms. - Jiménez-Castro, José Pablo (2014)
The objective of this study was to quantify the use of N in 11 dairy farms located in the provinces of San Jose, Cartago and Alajuela. Data such as feed purchases, milk sales, purchase and removal of animals was compiled and analyzed between January and December 2010. In order to evaluate the use of N, three indicators that allowed analyzing farm efficiency were used. Total number of animals ranged from 39 to 242. Annual milk production was 300880 kg with an average crude protein content that ranged between 3.08 and 3.39%. Farm area varied from 1 to 116 ha. The 11 farms imported on average 4636 (± 3491) kg of nitrogen, of which 75% came from feed and only 25% from fertilizers. Farms in turn exported 1572 (± 1177) kg of nitrogen, of which 93% was exported as milk and only 7% as animals. Also, total N exported ranged between 717 and 4716 kg, while farms imported 16.95 (± 7.37) g of N per kg of milk produced. In general, N balance was positive for all farms, indicating that more N entered the farm that came out in the form of product, showing that up to 65% of all imported N remained in the farms. Our results suggests that strategies to reduce N excretion should be developed, including improvements in the diet, since the largest N input is through imported feed.